Effect of collecting bee venom on the defensive behaviour of Apis mellifera - Sidana, V; Singh, J; Chhuneja, PK; Choudhary, A (Journal of the Hellenic Veterinary Medical Society, 2025)
Bees tend to sting the predator to defend its colony resources. In this action, alarm pheromone is also released which affect many colony activities. To determine the influence of weekly bee venom collection on the defensive behaviour of Apis mellifera Linnaeus colonies, experiments were conducted using two types of bee venom collectors (DPS-BVC-01 and Bee Whisper 5.0) on two bee strengths (8 and 16 bee-frames) during four seasons (monsoon, autumn, spring and summer) at Apis mellifera Apiary of Punjab Agricultural University, Ludhiana (India). Defensive behaviour of the colonies was recorded by swinging black leather ball in front of the colony entrance. One day after venom collection, defensive activity of the colonies (number of stings received on black leather ball per min) increased by 9.66 per cent compared to number of stings received one day before the venom collection, and decreased thereafter to be on par with pre-venom collection status after three days of venom collection. Among all the four seasons, the highest defensive response was observed during the summer season followed by in monsoon, spring and autumn seasons. During all the seasons, higher bee strength colonies stung more than weaker colonies, as 16 bee-frame strength colonies stung 37.42 per cent more than 8 bee-frame strength colonies. Further, the colonies exposed to DPS-BVC-01 (9 V) were 33.08 per cent more defensive than colonies exposed to Bee Whisper 5.0 (3 V) bee venom collector. However, exposure period (30 and 60 min) to venom collector did not show any significant difference in influencing the defensive behaviour of the honey bee colonies, thus venom can be safely collected from colonies.